Effects of Different Amounts of Supplemental Selenium and Vitamin E on the Incidence of Retained Placenta, Selenium, Malondialdehyde, and Thyronines Status in Cows Treated with Prostaglandin F2α for the Induction of Parturition. (7th November 2013) - Jovanović, Ivan B.; Veličković, Miljan; Vuković, Dragan; Milanović, Svetlana; Valčić, Olivera; Gvozdić, Dragan
Abstract : The incidence of retained placenta (RP) in cows increases in cases of parturition induced by prostaglandin F2 α . We analyzed the effects of different doses of supplemental selenium and vitamin E on the incidence of RP, blood selenium, plasma thyronines, and malondialdehyde concentration. Thirty-three clinically healthy, multiparous Holstein-Frisian cows were assigned to 3 groups and supplemented with a single intramuscular injection of sodium selenite (SS) and tocopherol acetate (TAc) between days 250 to 255 of gestation: control—unsupplemented; group A—10 mg SS + 400 mg TAc; group B—20 mg SS + 800 mg TAc. Parturition was induced using PGF2 α not before day 275 of gestation. The RP incidence was reduced from 66.7% in the control to 38.2 and 30.8% in groups A and B, respectively. Blood selenium and glutathione peroxidase activity in treated groups were significantly higher compared to control, with no significant difference between groups A and B. Plasma malondialdehyde in group B was significantly lower than that in control and group A, while thyronines levels were not affected. Comparison of RP and non-RP cows, independently of supplement treatment, revealed higher blood selenium and glutathione peroxidase activity and lower MDA and thyroxine in non-RP animals, while triiodothyronine level did not differ.